Overcoming water scarcity and quality constraints: Emergine Water Quality Problems in Developing Countries - van der Hoeck, Wim (International Food Policy Research Institute, 2001)
Safe water in sufficient quantities is fundamental to human health. The most important water-associated health problem is diarrehea, accounting for 3 to 5 million deaths per year, especially among children.